\(\frac{3}{5}\left(x-\frac{5}{6}\right)-\frac{1}{2}\left(\frac{3}{2}-1\right)=-\frac{1}{4}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.
\(\frac{2x+3}{4}-\frac{5x+3}{6}=\frac{3-4x}{12}\)
\(MC:12\)
Quy đồng :
\(\Rightarrow\frac{3.\left(2x+3\right)}{12}-\left(\frac{2.\left(5x+3\right)}{12}\right)=\frac{3x-4}{12}\)
\(\frac{6x+9}{12}-\left(\frac{10x+6}{12}\right)=\frac{3x-4}{12}\)
\(\Leftrightarrow6x+9-\left(10x+6\right)=3x-4\)
\(\Leftrightarrow6x+9-3x=-4-9+16\)
\(\Leftrightarrow-7x=3\)
\(\Leftrightarrow x=\frac{-3}{7}\)
2.\(\frac{3.\left(2x+1\right)}{4}-1=\frac{15x-1}{10}\)
\(MC:20\)
Quy đồng :
\(\frac{15.\left(2x+1\right)}{20}-\frac{20}{20}=\frac{2.\left(15x-1\right)}{20}\)
\(\Leftrightarrow15\left(2x+1\right)-20=2\left(15x-1\right)\)
\(\Leftrightarrow30x+15-20=15x-2\)
\(\Leftrightarrow15x=3\)
\(\Leftrightarrow x=\frac{3}{15}=\frac{1}{5}\)
1,\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{3}{7}.\left(7-\frac{1}{6}\right)+\frac{1}{3}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{3}{7}.\frac{41}{6}+\frac{1}{3}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{41}{14}+\frac{1}{3}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{137}{42}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)=\frac{137}{42}-\frac{1}{2}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)=\frac{58}{21}\)
\(\left(x-\frac{9}{4}\right)=\frac{5}{2}:\frac{2}{9}\)
\(\left(x-\frac{9}{4}\right)=\frac{45}{4}\)
\(x=\frac{45}{4}+\frac{9}{4}\)
\(x=\frac{27}{2}\)
a) \(\left|x\right|+\frac{1}{4}=\frac{1}{5}\)
\(\left|x\right|=\frac{1}{5}-\frac{1}{4}\)
\(\left|x\right|=\frac{-1}{20}\)(vô lý vì \(\left|x\right|\ge0\)với mọi x . Mà \(\frac{-1}{20}\)>0 )
Vậy không tồn tại x
b)\(\left|x+2\right|-\frac{1}{12}=\frac{1}{4}\)
\(\left|x+2\right|=\frac{1}{4}+\frac{1}{12}\)
\(\left|x+2\right|=\frac{1}{3}\)
\(\Rightarrow x+2\varepsilon\left\{\frac{1}{3};\frac{-1}{3}\right\}\)
+)\(x+2=\frac{1}{3}\Rightarrow x=\frac{-5}{3}\) +)\(x+2=\frac{-1}{3}\Rightarrow x=\frac{-7}{3}\)
Vậy \(x=\frac{-5}{3}\)hoặc \(x=\frac{-7}{3}\)
c)\(\left|x+5\right|=\frac{1}{7}-\left|\frac{4}{3}-\frac{1}{6}\right|\)
\(\left|x+5\right|=\frac{1}{7}-\frac{7}{6}\)
\(\left|x+5\right|=\frac{-43}{42}\)( vô lý vì \(\left|x+5\right|\ge0\)với mọi x , mà \(\frac{-43}{42}< 0\))
Vậy không tồn tại x
d)\(\left|x+\frac{5}{6}\right|=\left|\frac{1}{5}-\frac{2}{3}\right|+\frac{-3}{4}\)
\(\left|x+\frac{5}{6}\right|=\frac{7}{15}+\frac{-3}{4}\)
\(\left|x+\frac{5}{6}\right|=\frac{-17}{60}\)( Vô lý vì \(\left|x+\frac{5}{6}\right|\ge0\)với mọi x mà \(\frac{-17}{60}< 0\))
Vậy không tồn tại x
\(\frac{3}{5}.\left(x-\frac{5}{6}\right)-\frac{1}{2}.\left(\frac{3}{2}-1\right)=\frac{-1}{4}\)
\(\frac{3}{5}.\left(x-\frac{5}{6}\right)-\frac{1}{2}.\frac{1}{2}=\frac{-1}{4}\)
\(\frac{3}{5}.\left(x-\frac{5}{6}\right)-\frac{1}{4}=\frac{-1}{4}\)
\(\frac{3}{5}.\left(x-\frac{5}{6}\right)=\frac{-1}{4}+\frac{1}{4}\)
\(\frac{3}{5}.\left(x-\frac{5}{6}\right)=0\)
\(x-\frac{5}{6}=\frac{3}{5}:0\)
\(x-\frac{5}{6}=0\)
\(x=0+\frac{5}{6}\)
\(x=\frac{5}{6}\)
\(\frac{3}{5}\left(x-\frac{5}{6}\right)-\frac{1}{2}\left(\frac{3}{2}-1\right)=\frac{-1}{4}.\)
\(\left(\frac{3}{5}x-\frac{3}{5}\cdot\frac{5}{6}\right)-\left(\frac{1}{2}\cdot\frac{3}{2}-\frac{1}{2}\cdot1\right)=\frac{-1}{4}\)
\(\left(\frac{3}{5}x-\frac{1}{2}\right)-\left(\frac{3}{4}-\frac{1}{2}\right)=\frac{-1}{4}\)
\(\frac{3}{5}x-\frac{1}{2}-\frac{1}{4}=\frac{-1}{4}\)
\(\frac{3}{5}x=\frac{-1}{4}+\frac{1}{2}+\frac{1}{4}=\frac{1}{2}\)
\(x=\frac{1}{2}:\frac{3}{5}=\frac{5}{6}.\)